Análise de expressão gênica de membros da família SAUR durante a embriogênese somática de Coffea arabica - Zanin, Fabiana Couto (2017)
Considering the importance of the somatic embryogenic process for a large-scale production of selected embryos and for genetic improvement research, the present work aimed to characterize the SAUR genes in Coffea canephora and to analyze the transcriptomic profile of some of its members during somatic embryogenesis, additionally to speculate their functions. A in silico analysis of the genic family was performed by comparison of protein data of previously characterized SAURs in other species with the Coffee Genome Hub database, the sequences obtained went through redundancy and conserved domains analysis. A library of C. arabica transcripts was constructed from non-embryogenic callus (CNE), embryogenic callus (EC) and cell suspensions (ECS) cDNA sequenced samples, where differentially expressed SAUR genes were identified. The expression profile was analyzed by RT-qPCR in samples of C. arabica. 31 members of the SAUR family were found in coffee, of which, 8 were found to be differentially expressed in the sequenced libraries. The profile of SAUR5, 12, 13, 18 and 20 genes were analyzed in vivo in the present work. Further studies are needed to determine the functions of each of the genes analyzed during somatic embryogenesis, but the results seem to be in agreement with other studies, where SAUR genes are auxin-induced and are largely involved with expansion and cell elongation.